If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 77x = 44x + 6 Reorder the terms: 3 + 77x = 6 + 44x Solving 3 + 77x = 6 + 44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44x' to each side of the equation. 3 + 77x + -44x = 6 + 44x + -44x Combine like terms: 77x + -44x = 33x 3 + 33x = 6 + 44x + -44x Combine like terms: 44x + -44x = 0 3 + 33x = 6 + 0 3 + 33x = 6 Add '-3' to each side of the equation. 3 + -3 + 33x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 33x = 6 + -3 33x = 6 + -3 Combine like terms: 6 + -3 = 3 33x = 3 Divide each side by '33'. x = 0.09090909091 Simplifying x = 0.09090909091
| 32-15x=-18+9 | | 11/10=y/12 | | 4k+33=1-3k | | 8g-5w=4 | | a/10=4/9 | | 4a^9+5=8 | | 7+5y-4=6y+6-2y | | 3*(3-x)=5x+27 | | 7x-42=2x+12 | | 4x+10=-35-5 | | 1j^5-7=12 | | X-10=-4X | | 5b^2-36b=32 | | a+f=10 | | 1k+q=8 | | 3+10x=-6+x | | 2x-4=5x-12 | | 47x+(-13y)=0 | | 2t+2s=3b | | 36=96%.x | | 36=96%xX | | y=-8x+400 | | 2530=15 | | 7(7-3)=-u+11 | | 36=96%*x | | 404=27x+80 | | -.5(2y+5)=0.5(-7-4y) | | 5x+2=33 | | 9z+5=3 | | 4(5y+3)=22-6y | | 3(2.5-1.1)=2(5.2-3.3d) | | x+3x+1=21 |